Mentalizing Bodies: Explicit Mentalizing Without Words in Psychotherapy - Jensen, Thomas Wiben; Høgenhaug, Stine Steen; Kjølbye, Morten; Bloch, Marie Skaalum (Frontiers in Psychology, 2021)
Introduction: Mentalization concerns the human ability to understand the actions of others (and oneself) in terms of intentional mental states. Theoretically, the notion has been described via the poles of automatic, non-verbal implicit mentalization as opposed to conscious and verbal explicit mentalization. In this article, we challenge this standard distinction by examining examples from psychotherapy. We argue that explicit mentalization can also be carried out via embodied non-verbal actions. Method: Four cases of real-life interaction from psychotherapy sessions are analyzed from the qualitative perspective of embodied cognition and multimodal interaction analysis. The analyses are based on video data transformed into transcriptions and anonymized drawings from a larger cognitive ethnography study conducted at a psychiatric hospital in Denmark. Results: The analyses demonstrate the gradual development from predominantly implicit mentalizing to predominantly explicit mentalizing. In the latter part of the examples, the mentalizing activity is initiated by the therapist on an embodied level but in an enlarged and complex manner indicating a higher level of awareness, imagination, and reflection. Thus, the standard assumption of explicit mentalization as contingent on verbal language is challenged, since it is demonstrated how processes of explicit mentalization can take place on an embodied level without the use of words. Conclusion: Based on real-life data, the study demonstrates that online processes of implicit and explicit mentalization are gradual and interwoven with embodied dynamics in real-life interaction. Thus, the analyses establish a window into how mentalization is carried out by psychotherapists through interaction, which testifies to the importance of embodied non-verbal behavior in psychotherapy. Further, informed by the notion of affordance-space, the study points to alternative ways of conceptualizing the intertwined nature of bodies and environment in relation to conveying more complex understandings of other people.